Neurogenic Bladder - Peter T. Dorsher; Peter M. McIntosh (Advances in Urology)
Congenital anomalies such as meningomyelocele and diseases/damage of the central, peripheral, or autonomic nervous systems may produce neurogenic bladder dysfunction, which untreated can result in progressive renal damage, adverse physical effects including decubiti and urinary tract infections, and psychological and social sequelae related to urinary incontinence. A comprehensive bladder-retraining program that incorporates appropriate education, training, medication, and surgical interventions can mitigate the adverse consequences of neurogenic bladder dysfunction and improve both quantity and quality of life. The goals of bladder retraining for neurogenic bladder dysfunction are prevention of urinary incontinence, urinary tract infections, detrusor overdistension, and progressive upper urinary tract damage due to chronic, excessive detrusor pressures. Understanding the physiology and pathophysiology of micturition is essential to select appropriate pharmacologic and surgical interventions to achieve these goals. Future perspectives on potential pharmacological, surgical, and regenerative medicine options for treating neurogenic bladder dysfunction are also presented.